2016
DOI: 10.1017/s0014479716000119
|View full text |Cite
|
Sign up to set email alerts
|

THE RATIO OF CO2–C EMISSION TO GRAIN YIELD IN SUMMER MAIZE CULTIVATED UNDER DIFFERENT SOIL TILLAGE AND STRAW APPLICATION CONDITIONS

Abstract: SUMMARYThe relationship between climate, crop growth and crop yield is complicated. This study aimed to determine the ratio of CO2–C emission to grain yield, the field treatments were initiated in 2003, but the measurements for this analysis were collected during the summer maize-growing seasons of 2011 and 2012 in the North China Plain. The experiment showed that conventional tillage with straw application significantly increased grain yield and the ratio of CO2–C emission to grain yield of summer maize. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Straw retention can also increase the rate of soil CO 2 emission, which also increases the proportion of CO 2 emission per grain yield. The data presented herein show that NT could significantly reduce the CO 2 emission per grain yield 7 , 14 . Further, the analysis of Cd and Ct showed that SS S treatment not only absorbed a large amount of C, but also transported more C into the grain yield.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Straw retention can also increase the rate of soil CO 2 emission, which also increases the proportion of CO 2 emission per grain yield. The data presented herein show that NT could significantly reduce the CO 2 emission per grain yield 7 , 14 . Further, the analysis of Cd and Ct showed that SS S treatment not only absorbed a large amount of C, but also transported more C into the grain yield.…”
Section: Discussionmentioning
confidence: 68%
“…Thus, adopting agricultural best management practices (BMPs) can change SOC decomposition and CO 2 emission 4 , 5 . Tillage is one of the most important agricultural management practices to impact crop production 6 and alter SOC sequestration 2 along with changing CO 2 emission 7 . A primary management option to increase SOC storage therefore is to increase inputs of biomass-carbon (C) into the soil (i.e., retention of crop residues on the soil) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Zero tillage can effectively increase SOC and N storage in surface soil (Qi et al, 2019; Xue et al, 2018). This improvement may be caused by the cover crop residue, which could have helped in storing supplemental soil C and N; however, it could be caused by the lower C and N emission in a zero‐tillage system compared with that in a ploughing‐tillage system (Han, Ning, Li, & Cao, 2014; Lu & Liao, 2017). At the 10–20 cm soil depth, the SOC and N storage was higher in the PZT system in which the crop residue was buried about 20 cm deep.…”
Section: Discussionmentioning
confidence: 99%
“…Improved tillage measures and straw input could significantly affect the physical characteristics of soil, such as soil pH, soil nutrients, bulk density (Naresh, Dwivedi, Gupta, & Singh, ), soil temperature (Han et al., ; Ussiri & Lal, ) and soil water‐use efficiency (Bottinelli, Angers, Hallaire, Michot, & Guillou, ), which could subsequently improve the sustainable agricultural. As the climate warms up, forecasting the future feedbacks between soil carbon stocks and atmospheric CO 2 concentrations are strongly dependent on functions describing the response of SOM decomposition to temperature and moisture.…”
Section: Discussionmentioning
confidence: 99%
“…The sensitivity of these fractions might vary with site, temperature and moisture regimes, and management practices. Previous studies had demonstrated that soil tillage changes the soil physicochemical properties and affects heat movement in the soil, which subsequently affects soil temperature (Han, Ning, Li, & Cao, 2016;Ussiri & Lal, 2009); additionally, significant correlations between soil temperature and soil moisture content were revealed (Dong et al, 2017). Therefore, measuring the fractions of SOC and elucidating the interactive relationships among different SOC fractions may be indicative of tillage-induced changes in soil quality (Strosser, 2010).…”
mentioning
confidence: 99%